Utilizing performance parameters in wastewater treatment plants for the implementation of wastewater-based epidemiology - Morales Mora, Eric (2025)
Wastewater-based epidemiology (WBE) is an emerging tool for public health surveillance. It leverages the analysis of wastewater to monitor and detect various health-related indicators within a population. Contrasting traditional epidemiological methods, WBE avoids limitations such as participant recruitment and study selection biases, providing a comprehensive overview of community health. WBE is significant in public and environmental health as it enables the early detection of infectious diseases, substance use, and pollutant exposure. By analyzing the contents of wastewater, health officials can monitor the presence of pathogens, pharmaceutical residues, and biomarkers, thereby gaining insights into community health behaviors and conditions. This chapter outlines the principles and applications of WBE, highlighting its role in modern public health surveillance. It discusses the methodology of WBE, its implementation in different sanitation models, and its potential to monitor various health-related parameters. The structure of the chapter is as follows: The fundamentals of WBE explore the theoretical basis and practical applications of WBE in health surveillance. Sewerage infrastructure and WBE application describe different sewage management models and their relevance to WBE. Techniques for pathogen surveillance in wastewater detail the methods for detecting pathogens in wastewater, including sampling and laboratory analysis. Monitoring health-related chemical compounds in wastewater discusses the surveillance of pharmaceuticals, illicit drugs, and biomarkers through WBE. Statistical analysis and machine learning applied to WBE cover using statistical and machine learning techniques to interpret WBE data. Finally, implementing the WBE program provides a step-by-step guide to establishing and operating a WBE surveillance program.